The FT-Like ZCN8 Gene Functions as a Floral Activator and Is Involved in Photoperiod Sensitivity in Maize([C])([W])([OA]) - Meng, Xin (American Society of Plant Biologists, 2011)
The mobile floral-promoting signal, florigen, is thought to consist of, in part, the FT protein named after the Arabidopsis thaliana gene FLOWERING LOCUS T. FT is transcribed and translated in leaves and its protein moves via the phloem to the shoot apical meristem where it promotes the transition from vegetative to reproductive development. In our search for a maize FT-like floral activator(s), seven Zea mays CENTRORADIALIS (ZCN) genes encoding FT homologous proteins were studied. ZCN8 stood out as the only ZCN having the requisite characteristics for possessing florigenic activity. In photoperiod sensitive tropical lines, ZCN8 transcripts were strongly upregulated in a diurnal manner under floral-inductive short days. In day-neutral temperate lines, ZCN8 mRNA level was independent of daylength and displayed only a weak cycling pattern. ZCN8 is normally expressed in leaf phloem, but ectopic expression of ZCN8 in vegetative stage shoot apices induced early flowering in transgenic plants. Silencing of ZCN8 by artificial microRNA resulted in late flowering. ZCN8 was placed downstream of indeterminate1 and upstream of delayed flowering1, two other floral activator genes. We propose a flowering model linking photoperiod sensitivity of tropical maize to diurnal regulation of ZCN8.